Inonotus Obliquus Suppresses Proliferation of Colorectal Cancer Cells and Tumor Growth in Mice Models by Downregulation of β-Catenin/NF-κB-Signaling Pathways. (September 2013) - Mishra, S.K.; Kang, J-H.; Song, K-H.; Park, M.S.; Kim, D-K.; Park, Y-J.; Choi, C.; Kim, H.M.; Kim, M.K.; Oh, S.H.
Chaga mushroom (Inonotus obliquas) has been used as a folk remedy for several illnesses including gastrointestinal disorders. We recently reported the potent anti-inflammatory effect of chaga extract in experimental colitis. However, its effects on colorectal cancer (CRC) have not been clearly elucidated. We investigated the effects of an aqueous extract of Inonotus obliquus (IOAE) in vitro in HCT116 and DLD1 cell lines and in vivo for adenoma in APC Min/+ mice and colitis-associated colon cancer in AOM/DSS-treated mice. Results show that IOAE suppressed the proliferation of both cell lines, and inhibited the growth of intestinal polyps in APC Min/+ and colon tumors in AOM/DSS-treated mice. IOAE induced mitochondrial intrinsic pathway of apoptosis, autophagy, and S phase cell cycle arrest. IOAE suppressed the expression levels of iNOS and Cox-2 and mRNA levels of pro-inflammatory cytokines (IL-6, IL-1β, TNF-a and IFN-γ) in the intestine of mice models. IOAE suppressed the nuclear levels of β-catenin and inhibited its downstream targets (cyclin D1 and c-Myc) along with CRC oncogene CDK8. IOAE inhibited the expression of NF-κB at cytoplasmic and nuclear levels. Our results demonstrate that IOAE possess potent anti-inflammatory and anti-proliferative properties through downregulation of Wnt/β-catenin and NF-κB pathways. Considering recent anticancer approaches involving natural products with minimal side effects, we advocate that Inonotus obliquus could be a beneficial supplement in prevention of colorectal cancer.